Undergraduates’ knowledge, attitudes, and behaviours associated with fad diets - Andrea T. Kozak; Noah Garber; Virginia Uhley (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Purpose We aimed to determine undergraduate students’ use and knowledge of fad diets as well as examine how appealing students found these diets given the goal of rapid weight loss and/or improved health. Twenty-three students from a Midwestern university (mean age = 19.2, mean BMI = 27.35, 69.6% female) were recruited through new student orientations for this qualitative study. Approximately 52% of participants identified as White, 30% as Black, 13% as Asian, and 4% as multi-racial. Methods Knowledge and opinions about fad diets were collected via focus groups and individual interviews. Coding of transcripts was conducted by hand using the constant comparative method and data were analysed based on grounded theory. Results Two primary themes emerged: very negative views of fad diets and the importance of healthy eating. Although few participants had tried fad diets, they thought these diets: 1) did not lead to sustained weight loss, 2) were associated with disappointment and health issues, and 3) were money-making schemes delivered heavily through social media. Participants also valued healthy eating. Conclusion Experimental studies are needed to examine how healthy eating among university students can be supported through credible sources, accurate information, and established connections via innovative social media platforms.